2012
DOI: 10.1152/ajpendo.00087.2012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative expression of hCG β-genes in human trophoblast from early and late first-trimester placentas

Abstract: Human chorionic gonadotropin (hCG) displays a major role in pregnancy initiation and progression and is involved in trophoblast differentiation and fusion. However, the site and the type of dimeric hCG production during the first trimester of pregnancy is poorly known. At that time, trophoblastic plugs present in the uterine arteries disappear, allowing unrestricted flow of maternal blood to the intervillous space. The consequence is an important modification of the trophoblast environment, including a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…CGA and CGB are the two subunits of HCG, known to play a major role in pregnancy initiation and progression and are involved in trophoblast differentiation (20). The trend observed for these two genes was consistent with what is known from HCG levels during pregnancy (21). Free CGB and PAPPA are also used as biochemical markers for risk of Down syndrome in the first trimester (22).…”
Section: Resultssupporting
confidence: 67%
“…CGA and CGB are the two subunits of HCG, known to play a major role in pregnancy initiation and progression and are involved in trophoblast differentiation (20). The trend observed for these two genes was consistent with what is known from HCG levels during pregnancy (21). Free CGB and PAPPA are also used as biochemical markers for risk of Down syndrome in the first trimester (22).…”
Section: Resultssupporting
confidence: 67%
“…Moreover, we also observed that hypomethylated blocks distinguish villous cytotrophoblasts before and after they first come into contact with maternal blood (weeks 10-12), providing the first evidence of an isolated non-cancer cell type with large-scale hypomethylated blocks. Furthermore, the result indicates that our finding of hypomethylated blocks in the placenta is not an artifact of 11 cell-type confounding related to changes in cellular composition during pregnancy. It also suggests that many of the methylation differences between early and late pregnancy placenta are associated with changes in the cytotrophoblast microenvironment including exposure to components of maternal blood and higher oxygen tension.…”
Section: Discussionsupporting
confidence: 50%
“…The chorionic villus represents the structural and functional unit that projects from the fetal placenta to invade the maternal uterine lining. The villous core, made of fibroblasts, mesenchymal cells, Hofbauer cells and fetal-placental vessels, is covered by layers of villous cytotrophoblasts and syncytiotrophoblasts, which are in direct contact with maternal blood [11]. DNA methylation was measured on the 450k array and quantified using Beta values.…”
Section: Cpg-poor Genomic Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…gov/ij/) was used to quantify the immunoreactive bands, and the normalized antigen signals were calculated from target proteinderived and ␤-actin-derived signals. ␤hCG levels in serum-free culture supernatants of BeWo cells and CTBs were determined by Enzyme Immunometric Assay kit as described previously (21).…”
Section: Methodsmentioning
confidence: 99%